Opus heraldicum (Sumpt. Joannis Davidis Zunneri Typis Joh. Theodorici Fridgenii, 1680)
Polonicum: tab. 32 zawiera 2 herby królów polskich, na s. 688-700 o królach pol. i ks. śląskich
Egz. kompletniejszy niż 3597